Hubungan manajemen Industrial : Studi Literatur tentang Dinamika Kerja dan Kebijakan di Gojek: Industrial Management Relations: A Literature Review of Work Dynamics and Policies at Gojek - Handayani, Devyasri Nusa; Situmorang, Sangaviery Loucas (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The rapid development of information technology has driven the global economic transformation towards a digital economy, including in Indonesia. A tangible manifestation of this phenomenon is the emergence of online ride-hailing services like Gojek, which utilize digital platforms to connect service providers with consumers while simultaneously creating new job opportunities through a partnership system. This research aims to examine the work dynamics and industrial relations policies between the company and its Gojek driver-partners within the context of the gig economy. The method employed is a literature review, analyzing various academic sources related to digital labor relations. The findings indicate that while flexible working hours are a primary advantage of Gojek's work system, it also presents serious challenges, such as income uncertainty, a lack of social security, and the absence of formal legal protection for driver-partners. Work policies implemented unilaterally through the application reflect a power imbalance in the relationship between the company and its partners. Therefore, fairer, more transparent, and participatory policies are required to create a sustainable and equitable working relationship in the era of the digital economy.